Особистий бренд іт-спеціаліста - Соколова, В. К. (ХНУРЕ, 2023)
A personal brand is, quite simply, a presence—either online or offline—that represents you, your values, and what you have to offer. Your personal brand needs to be well thought-out, consistent, and true. No matter what field you’re in, a personal brand allows you to communicate your expertise, your experience, and your personality all at once. Ultimately, this tells people who you are, what you’re about, and why they should contact you. A personal branding statement tells people, in one or two sentences, who you are and what you’re about. There are three key components: Your job title, your expertise or the niche you’re zeroing in on, and something interesting about yourself—say, a special talent, or something unique that you bring to the table that could be helpful in your industry.